Evaluation of a Training Program Prototype to Promote the Adoption of Clinical Mental Health Assessment Best Practices Among Primary Care Nurses: A Research Protocol - Girard, Ariane; Lafontaine, Sarah; Lemée, Marie-Hélène; Carrier, Jean-Daniel; Beaudin, Jérémie; Arroyave, Luz Piedad; Abou Malham, Sabina; Sasseville, Maxime (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2025)
Introduction: Nurses play an essential role in the detection and assessment of mental health issues. However, adopting best assessment practices in mental health remains challenging for primary care nurses (PCN). Objectives: This article presents a study protocol aimed at evaluating the acceptability and the perceived effects of a training program prototype to enhance the adoption of best practices in mental health assessment by PCNs. Additionally, the study explores the feasibility of involving PCNs clinical supervisors in the training process. Methods: The 6-week training program was developed using a living lab approach, combining individual and group activities, focusing on reflective practice and clinical support. A mixed-methods approach combining quantitative and qualitative designs will be used, with data collected from 10 to 20 PCNs and 2 to 4 clinical supervisors. Five questionnaires will assess the acceptability of the program (following each activity), while perceived effects will be explored through 3 questionnaires at 3 time points: pre-, immediately post-, and 4 to 6 months post-program. Qualitative interviews will also be conducted with PCNs and PCN clinical supervisors (immediately post- and 4 to 6 months post-program) to explore the acceptability, perceived effects of the program and the feasibility of involving PCN clinical supervisors in the program. Discussion and Research Spin-offs: By evaluating the acceptability and perceived effects of this innovative continuing education program for mental health assessment, this project could provide valuable insights for adapting and testing the program in other settings and with a broader population.